Studies towards the development of label-free AC impedimetric immunosensors for healthcare and food quality control - Tsekenis, Georgios (Cranfield University, 2008)
This thesis describes work focused towards the fabrication and characterisation of immunosensor platforms for the label-free detection of analytes of importance in the health and food industries. Due to their low unit cost and ease of fabrication, the immunosensor market has significantly increased recently, resulting in a constant demand for new immunosensor applications. Within this thesis, therefore, a novel fabrication protocol is reported towards the production of immunosensor platforms for the detection of the antibiotic, ciprofloxacin, the stroke and multiple sclerosis marker, Myelin Basic Protein (MBP) and the ovarian cancer marker CA-125. Initial investigations were aimed towards the electrochemical characterization of the available electrode substrates at the onset of this research project namely, gold sputter coated, screen-printed gold and carbon electrodes. They showed that only carbon electrodes provide sufficiently reproducible results and thus these electrodes have been employed for immunosensor fabrication. Due to the advantages of microelectrodes over planar electrodes, attempts to fabricate microelectrode arrays were also made via the ultrasonic ablation of passivated electrode assemblies. For the site-specific immobilisation of antibodies on polymer modified surfaces biotin-neutravidin affinity technologies were used. The fabricated immunosensors were then interrogated upon exposure to antigen solutions utilising the technique of electrochemical impedance spectroscopy (EIS). Changes in the obtained impedance spectra were used to plot calibration profiles for the detection of ciprofloxacin in buffer and in milk. Similar profiles have been plotted for Myelin Basic Protein (MBP) and the ovarian cancer marker CA-125.